Print It To Me Development System - Dickenn, Haezel Ann; Ramli, Azizul Azhar; Ali Shah, Zuraini; Kasim, Shahreen (SOTVI, 2019)
This paper addresses the project where, by the end of the project, the web-based system is able to provide an online printing service system to any party or individual who are staying in-campus to make money with their personal printer. In-campus student and staff are allowed to register as service provider (SP) and they can view and accept order via this webbased system. The system are able to display and show requests by customers while the service providers can select the requests and provide proper service to them. Furthermore, the system should have limitless availability of access, compared to the current printing request process.